2007
DOI: 10.2478/s11536-007-0043-1
|View full text |Cite
|
Sign up to set email alerts
|

Obese and female adolescents skip breakfast more than their non-obese and male peers

Abstract: AbstractWe examined the association between overweight/gender and skipping breakfast among adolescent students in Tehran city using a cross-sectional study and a multistage random sampling method. All educational zones in Tehran city were covered during the educational year of 2000–01. In total, 2321 students aged 11–16 years (1068 male; 1263 female) participated in the study. Weight and height were measured and body mass index (BMI; kg/m2) was calculated. Overweight, pre-obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(34 reference statements)
2
5
0
Order By: Relevance
“…Consistent with previous research, adolescent girls ate breakfast on fewer days per week compared to boys [ 13 , 34 , 35 ]. Despite the evidence that adolescents who skip breakfast are more likely to be overweight than those who regularly eat breakfast [ 5 ], skipping breakfast may be a chosen method of weight control for girls, and in some individuals may be associated with dieting, or disordered eating [ 35 ]. Further research is needed to understand the gender differences in breakfast consumption.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous research, adolescent girls ate breakfast on fewer days per week compared to boys [ 13 , 34 , 35 ]. Despite the evidence that adolescents who skip breakfast are more likely to be overweight than those who regularly eat breakfast [ 5 ], skipping breakfast may be a chosen method of weight control for girls, and in some individuals may be associated with dieting, or disordered eating [ 35 ]. Further research is needed to understand the gender differences in breakfast consumption.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous past studies have identified that it is common for women to skip breakfast, and that skipping breakfast is associated with overweight and obesity (Keski- Rahkonen, Kaprio, Rissanen, Virkkunen, & Rose, 2003; Rashidi et al, 2007; Timlin, Pereira, Story, & Neumark-Sztainer, 2008). Thus, being married may be a protective factor for eating breakfast daily, which is a known protective factor for overweight/obesity (Keski-Rahkonen et al, 2003; Rashidi et al, 2007). One might expect this finding to be related to the fact that married women are also more likely to be parents.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, skipping breakfast is typically more prevalent among girls (41,42) . This gender difference is not fully understood, and it was often explained by the higher weightrelated concerns among girls compared with boys (43,44) . The girls in our survey reported that lack of hunger and appetite in the morning was the main reason to skip breakfast.…”
Section: Breakfast Intakementioning
confidence: 99%